Comparison of whole trunk muscle mass between healthy and lumbar herniated nucleus pulposus patients using abdominal pelvic computed tomography - Oh, Chi-Hoon; Shin, Dong-Eun; Yoon, Siyeong; Oh, Jongbeom; Lee, Younghun; Lee, Soonchul (Frontiers in Medicine, 2023)
Paraspinal muscle asymmetry is associated with low back pain (LBP) problems. This study aimed to analyze skeletal muscle areas around the lumbar vertebra and compare the ratio of anterior and posterior muscles between patients with lumbar herniated nucleus pulposus (HNP) and healthy individuals using abdominal pelvic computed tomography (APCT).After propensity score matching, 122 HNP patients and 122 non-HNP individuals were finally used for analyses. . In APCT, axial cut images were collected at the level of the third lumbar vertebra lower end plate and only the muscle structure was obtained. After obtaining the muscular portion of their image, we measured the skeletal muscle area (SMA). Second, for analysis relation of sarcopenia and HNP, the status of low skeletal muscle mass was determined using a previously reported criteria based on APCT scans in the Republic of Korea.From the analysis of the anterior-posterior muscles, the ratio of anterior SMA was statistically significantly larger in the HNP group than in the non-HNP group. Regarding the anatomical classification of trunk muscles, a statistically significant left-right imbalance to peripheral muscle in HNP men was observed. Regarding the status of low skeletal muscle mass, no statistical difference in prevalence between the two groups were observed. Moreover, no statistical difference in the prevalence of low skeletal muscle mass obesity was observed.The lumbar flexor muscle was larger in HNP than others, showing trunk muscle imbalance. However, low skeletal muscle mass is not associated with HNP.